2021
DOI: 10.4018/978-1-7998-6428-8.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Travel by People With Physical Disabilities

Abstract: It is acknowledged that access to tourism by persons with disabilities continues to be shaped by a variety of constraints that are not being clearly or consistently addressed by those in charge of tourism planning and management. Based on these assumptions, this chapter is focused on the identification of structural constraints and negotiation strategies that influence the decision and participation to travel for people with physical disabilities. To achieve these objectives, the chapter used a qualitative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Blichfeldt and Nicolaisen, 2011; Daniels et al , 2005; Devile and Kastenholz, 2018; Yau et al , 2004). It was also possible to confirm the attention given by respondents to other details regarding travel organization, such as support services, packing, medication, and food provision as was also noted by Blichfeldt and Nicolaisen (2011), Devile and Moura (2021), among others. The following testimonies presented some examples, which illustrate different travel requirements and concerns:… to take all my medication.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Blichfeldt and Nicolaisen, 2011; Daniels et al , 2005; Devile and Kastenholz, 2018; Yau et al , 2004). It was also possible to confirm the attention given by respondents to other details regarding travel organization, such as support services, packing, medication, and food provision as was also noted by Blichfeldt and Nicolaisen (2011), Devile and Moura (2021), among others. The following testimonies presented some examples, which illustrate different travel requirements and concerns:… to take all my medication.…”
Section: Resultsmentioning
confidence: 64%
“…For this, PwSN have to do an intensive information search, especially regarding the requirements to meet their specific needs. Thus, it was found that rigorous and thorough planning of the whole trip (from the time they leave home until they return) is the main key to a satisfactory tourist experience (Daniels et al , 2005; Devile and Kastenholz, 2018; Devile and Moura, 2021; Nyman et al , 2018). This is transversal to all respondents and covers both issues about tourism sector and other services (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations